Komunikasi Dalam Wilayah Pembangunan dan Pemberdayaan Masyarakat - Yudhatama, Iranda; Virgo Kartika, Widyaningtyas (Jurnal Ilmu Komunikasi AKRAB, 2025)
In the context of development and community empowerment and social change, academics and practitioners may differ somewhat regarding the terminology and definitions they use regarding the role and function of communication. However, in substance, they can be said to be relatively similar, namely, that development and community empowerment programs cannot produce social change without ongoing and socially and culturally relevant communication activities between the implementing agency for the development or community empowerment program and the beneficiary groups of the program Based on this context, this article attempts to explain the relationship between communication science and community empowerment and the role of communication in community empowerment programs through literature studies. Some of the literature that became the main study materials were books, including Designing Messages for Development Communication; An Audience Participation Based Approach, (Mody, 1998); Diffusions of Innovations, 5th Edition,(Rogers, 2003); Communication for Development and Social Change, (Servaes, 2008) and several journal articles. The results of the study show that communication is a very important factor in community empowerment, and in theory and practice there are at least three communication models that are often used, namely; (1) the innovation diffusion model; (2) the participatory communication model and (3) the ethnographic communication model.